Student transition into higher education: Time for a rethink within the subject of sport and exercise science? - Timmis, Matthew A.; Pexton, Sharon; Cavallerio, Francesca (Frontiers in Education, 2022)
The first year of higher education (HE) marks one of the most significant transitions in a student's life. Within the U.K., the subject area of Sport and Exercise Science (SES) has a problem with effectively supporting and retaining students as they transition into HE. If students’ capabilities to successfully transition are to be fully understood and resourced, it is necessary for research to foreground students’ lived realities.  Utilising letter to self-methodology, 58 second- and third-year undergraduate SES students wrote to their younger self, providing guidance on how to successfully transition into HE. Data were analysed using reflexive thematic analysis. Six themes and four sub-themes were identified. Following the development of a single composite version of an ‘Older, wiser self letter’ to represent the identified themes, this resource was integrated into the institution’s pastoral care resources and sessions where personal tutors connected with their tutees. Student member reflections were completed to gather feedback regarding the resource’s effectiveness. The composite letter provides an authentic account of how to face obstacles encountered as students transition into HE. Students’ member reflections highlighted that the letter was a valuable resource as a prompt for discussion regarding their experiences of transitioning into HE. When in the student journey the letter was read was particularly important. The value of this composite letter lies in the implementation of tutor-tutee and student peer-peer conversations at key ‘moments’ throughout their journey in HE, helping students understand the challenges and opportunities for success during transition.